9,10-Dioxoanthracenyldithiocarbamates effectively inhibit the proliferation of non-small cell lung cancer by targeting multiple protein tyrosine kinases - Mateusz Olszewski; Maryna Stasevych; Viktor Zvarych; Natalia Maciejewska (Journal of Enzyme Inhibition and Medicinal Chemistry)
Anthraquinones have attracted considerable interest in the realm of cancer treatment owing to their potent anticancer properties. This study evaluates the potential of a series of new anthraquinone derivatives as anticancer agents for non-small-cell lung cancer (NSCLC). The compounds were subjected to a range of tests to assess their cytotoxic and apoptotic properties, ability to inhibit colony formation, pro-DNA damage functions, and capacity to inhibit the activity of tyrosine kinase proteins (PTKs). Based on the research findings, it has been discovered that most active derivatives (i84, i87, and i90) possess a substantial capability to impede the viability of NSCLC while having mostly a negligible effect on the human kidney cell line. Moreover, the anthraquinones displayed pro-apoptotic and genotoxic attributes while blocking the phosphorylation of multiple PTKs. Collectively, our findings indicate that these derivatives may demonstrate promising potential as effective anticancer agents for lung cancer treatment.